Analisis Tingkat Keramah Lingkungan Alat Tangkap Purse Seine yang Berpangkalan di Pelabuhan Perikanan Samudera (PPS) Nizam Zachman Jakarta Utara - Sendy Wicaksono; M Tajuddin Noor; Exist Saraswati (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
It is absolutely essential to use environmentally friendly fishing gear that complies with the Code of Conduct for Responsibility (CCRF FAO 1995). This is due to the impact of using non-environmentally friendly fishing gear in the form of environmental damage. Competition between fishing gears to get maximum catches raises concerns about overfishing. Therefore, environmentally friendly fishing gear is a reference in the use of technology and fishing gear. Purse seines are a type of fishing gear that is widely operated, this fishing gear is operated with a single vessel or single Purse Seine boat. The aim of this research is to analyze the level of environmental friendliness of purse seines. Data was obtained using the interview method with 30 respondents.